Normativa jurídica que regula la tipicidad específica de la pornografía infantil publicada a través de redes sociales en la ciudad de pasaje en el periodo 2013. - Morocho Noles, Magaly Lucía (2014)
In the present investigation, we have defended the idea that lack specific typicality of child pornography published through social networks creates difficulties for the investigation of this crime, as well as the allocation of assets subject and therefore, impunity. We also demonstrated that fundamental rights are injured by child pornography published through social networks are all those who are concerned with the moral aspects of society, especially sexual morality and the free development of personality, mainly in children who exchange information through social networks. Once you consolidate those ideas through their demonstration a proposal with much certainty has yet to solve the ongoing conflict was performed.